A taxonomic revision of the Yasuni Round-eared bat, Lophostoma yasuni (Chiroptera: Phyllostomidae) - Camacho, M. Alejandra; Chávez, Daniel; Burneo, Santiago F. (Zootaxa, 2016)
The Yasuni Round-eared bat, Lophostoma yasuni, was described in 2004 by morphological analysis of the holotype, the only specimen attributed to this taxon to date. A molecular analysis using cytochrome-b sequences and a new morpholo-gical analysis that includes the holotype of L. yasuni and two specimens of L. carrikeri from near the type locality of L. yasuni were carried out. The new molecular and morphological evidence places L. yasuni within the clade of L. carrikeri. We propose that L. yasuni should therefore be considered as a synonym of L. carrikeri. An emended diagnosis for L. carrikeri extending ranges of craniodental measurements for this species is presented.